Mild Renal Dysfunction Among Turkish Adults: Prevalence and Its Association With Insulin Resistance - Onat, Altan; Yazici, Mehmet; Hergenc, Gulay; Uyarel, Huseyin; Esen, A. Metin; Karabulut, Ahmet; Can, Gunay (TURK NEFROLOJI DIYALIZ TRANSPLANTASYON DERGISI, 2006)
Objectives: To investigate the prevalence of mild renal dysfunction and its association with insulin resistance (IR), metabolic syndrome (MS) or its components among Turkish adults. Methods: Serum creatinine concentrations were measured in 1048 male and female subjects. After excluding cases with diabetes mellitus, 933 participants of a representative cohort were studied cross-sectionally. Glomerular filtration rate (GFR) was estimated based on serum creatinine concentrations using the Modification of Diet in Renal Disease formula. GFR was divided into 3 categories constituting chronic kidney disease stages 2 and 3 3. MS was identified by modified criteria of the Adult Treatment Panel-III. Results: MS existed in 38.7% of the cohort. Mild renal dysfunction (estimated GFR 60 to 89.9 mL/min/1.73 m(2)) existed in 50% of the study sample in both genders. Compared to the group with normal GFR, in category II, age-adjusted estimates of body mass index, homeostatic model assessment (HOMA) index, blood pressures, total, HDL-, LDL-cholesterol and serum proteins were all significantly elevated in both genders, as were apo B and log TSH in women alone. Stated variables were also significantly and inversely correlated with GFR. Whereas MS was not significantly associated with GFR categories, nor with reduced GFR when controlled for HOMA, HOMA D adjusted for MS as well as for sex, age and systolic BP-was significantly associated with likelihood for reduced GFR. Conclusions: Mild impairment of kidney function is very common in nondiabetic middle-aged and elderly adults, is associated mainly with IR and related cardiovascular risk factors, in the absence of MS-related atherogenic dyslipidemia. IR is important even in mild reduction in GFR, an action independent of central obesity-related components of MS.
Keywords: dyslipidemia; glomerular filtration rate; kidney dysfunction; insulin resistance; metabolic syndrome; population-based study; CHRONIC KIDNEY-DISEASE; GLOMERULAR-FILTRATION-RATE; CARDIOVASCULAR-DISEASE; ELDERLY PERSONS; PLASMA-LIPIDS; RISK; POPULATION; HYPERINSULINEMIA; CHOLESTEROL; Urology & Nephrology